Voluntary 'donations' versus reward-oriented 'contributions': Two experiments on framing in funding mechanisms - Maja Adena; Steffen Huck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
In an artefactual field experiment, we implemented a crowdfunding campaign for an institute's summer party and compared donation and contribution framings. We found that the use of the word 'donation' generated higher revenue than the use of 'contribution'. While the individuals receiving the donation framing gave substantially larger amounts, those receiving the contribution framing responded more strongly to reward thresholds and suggestions. An additional survey experiment on MTurk indicated that the term 'donation' triggers more positive emotional responses and that emotions are highly correlated with giving. It appears that making a donation is perceived as a more voluntary act and is thus more successful at generating warm glow than making a contribution. We surmise that this extends to other funding mechanisms.
Keywords: C93; D64; D12; 330; crowdfunding; field experiment; framing